Gender and power relation in English refusal strategies of ESL undergraduates - Nurul ‘Aqiilah Mohd Kamal,; Adlina Ariffin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Refusal refers to a face-threatening act (FTA) which may put one’s self esteem at risk in communication. It encompasses turning down someone’s request, offer or suggestion. The speech act of refusal has been one of the most prominent areas of interest for many scholars. However, there is a dearth of such study particularly within the Malay community. Thus, this study examined the refusal strategies used by Malay undergraduates in the context of English as a Second Language (ESL), observed the differences and similarities in the refusal strategies of male and female undergraduates, and analysed the influence of relative power on the choice of their refusal strategies. This study employed the Discourse Completion Test (DCT) which was distributed among sixty Malay ESL undergraduates, consisting of 30 males and 30 females where they were required to refuse requests from three addressees (lecturer, friend, junior) in five different situations. The collected data were then analysed quantitatively. The findings showed that 32 out of 41 types of refusal strategies were used by the participants such as statements of regret, excuse and reason. Both male and female students employed indirect refusal strategies regardless of the person’s relative power. However, in using direct refusal strategies, females tended to be more direct in stating their refusals than males. The findings of this study will provide new insights on the pragmatic competence of Malay ESL undergraduates in employing refusal strategies in English, specifically when different gender and relative power are deployed in communication.